Peran Locus of Control, Pengetahuan Keuangan dan Sikap Keuangan dalam Membentuk Perilaku Keuangan Mahasiswa di Kota Langsa - Fuad, Muhammad; Murni, Cici Dewi Sari; Safrizal, Safrizal; Salman, Muhammad; Wahyu, Muhammad (Jurnal Samudra Ekonomi dan Bisnis, 2025)
The study analyzes the role of locus of control, financial knowledge and financial attitudes towards students' financial behavior. Furthermore, locus of control is divided into internal locus of control and external locus of control. The sample consisted of 280 students in Langsa City. The data analysis method used multiple linear regression. The results showed that internal locus of control, external locus of control and financial knowledge were proven to have a partial significant effect on students' financial behavior, but financial attitudes were identified as having no significant effect on the behavior. Simultaneously, all independent variables in this study were proven to have a significant effect on financial behavior. The results of the coefficient of determination showed that the four independent variables in this research model only contributed little to explaining the variations that occurred in students' financial behavior in Langsa City.